2023
DOI: 10.3390/s23052547
|View full text |Cite
|
Sign up to set email alerts
|

Self-Monitoring Diabetes-Related Foot Ulcers with the MyFootCare App: A Mixed Methods Study

Abstract: People with diabetes-related foot ulcers (DFUs) need to perform self-care consistently over many months to promote healing and to mitigate risks of hospitalisation and amputation. However, during that time, improvement in their DFU can be hard to detect. Hence, there is a need for an accessible method to self-monitor DFUs at home. We developed a new mobile phone app, “MyFootCare”, to self-monitor DFU healing progression from photos of the foot. The aim of this study is to evaluate the engagement and perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The medium-term goal remains the initial deployment for doctors, with the ultimate aim of creating a patient application. This approach is aligned with the research conducted by Plonderer et al [61], which emphasizes the utilization of such tools in collaboration with healthcare experts.…”
Section: Discussionmentioning
confidence: 68%
“…The medium-term goal remains the initial deployment for doctors, with the ultimate aim of creating a patient application. This approach is aligned with the research conducted by Plonderer et al [61], which emphasizes the utilization of such tools in collaboration with healthcare experts.…”
Section: Discussionmentioning
confidence: 68%
“…Studies ranging from early detection and prevention to self-monitoring apps collectively highlight the potential of mHealth in improving patient outcomes, and addressing challenges in diabetes care [48]. We are expecting that similar to other studies a difference in knowledge pretest and posttest knowledge score will be observed [49,50] and that the app will be perceived as valuable [22,24,25,27,28,51]. However, as the learning curriculum included in Well Feet app is much more comprehensive than in other solutions and encompasses multilevel tailoring mechanisms such as notifications for learning reinforcement and adaptive learning pathway for knowledge gaps identification, we are expecting that the foot care knowledge and behavior results will differ from other studies.…”
Section: Principal Findingsmentioning
confidence: 64%
“…Furthermore, in this study we are aiming at in app exploring usage patterns among the participants, especially those who experienced knowledge or behavior change. Ploderer et al [51] has observed 3 usage patterns when evaluating a wound care tracking app: continuous, temporary, and failing usage. In our study, it is expected that some barriers to usage identified by Ploderer et al [51] will overlap, especially the ones leading to temporary usage such as work commitments and health disruptions.…”
Section: Principal Findingsmentioning
confidence: 99%
“…We encourage clinical researchers to conduct studies that investigate educational or psychological interventions intended to improve outcomes of offloading interventions, especially since educational and psychological interventions have shown promise in other areas of diabetes and diabetes-related foot disease, such as for self-care and footwear adherence for ulcer prevention. [48][49][50][51][52] Clinical question 14: In a person with diabetes and a foot ulcer, should an offloading intervention for the contralateral limb along with an offloading intervention for the ipsilateral limb be used over only an offloading intervention for the ipsilateral limb? Recommendation 10: In a person with diabetes and a foot ulcer for which a knee-high or ankle-high offloading device is used, consider also using a shoe lift on the contralateral limb to improve the person's comfort and balance with walking in the device (Conditional;…”
Section: Rationalementioning
confidence: 99%
“…However, despite this lack of evidence, we consider this question is an important one. We encourage clinical researchers to conduct studies that investigate educational or psychological interventions intended to improve outcomes of offloading interventions, especially since educational and psychological interventions have shown promise in other areas of diabetes and diabetes‐related foot disease, such as for self‐care and footwear adherence for ulcer prevention 48–52 …”
Section: Recommendationsmentioning
confidence: 99%